Progress in nanophotonics 1 - Ohtsu, Motoichi (Nano-Optics and nanophotonics, 2011)
This book focuses on the recent progress in nanophotonics technology to be used to develop novel nano-optical devices, fabrication technology, and security systems. It begins with a review of the concept of dressed photons and applications to devices, fabrication, and systems; principles and applications. Further topics include: DNA process for quantum dot chain, photon enhanced emission microscopy, near field spectroscopy of metallic nanostructure, self-organized fabrication of composite semiconductor quantum dots, formation of metallic nanostructure, and nanophotonic information systems with security. These topics are reviewed by seven leading scientists. This overview is a variable resource for engineers and scientists working in the field of nanophotonics.